Tennis Court Facility Management: Maintenance, Utilization, and Safety (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to conduct a comprehensive literature review on tennis court facility management, focusing on three main aspects: maintenance, utilization, and user safety. Through a literature review, 20 articles published between 2015 and 2025 were analyzed using the PRISMA approach to examine the quality of court physical maintenance, facility utilization optimization, and injury risk mitigation practices. The study results indicate that surface maintenance, including routine cleaning, crack repair, and improved drainage, is a key factor in maintaining court durability. Regarding utilization, systematic scheduling and regulating usage intensity can reduce wear and tear and improve facility efficiency. Meanwhile, user safety is significantly affected by surface conditions, lighting, and court level, with most injuries associated with slippery or uneven surfaces. The study also found that key challenges in facility management include budget constraints, a lack of trained personnel, and inconsistent implementation of standard operating procedures (SOPs) across institutions. The use of modern technologies such as surface sensors, humidity monitoring devices, and digital-based facility management systems are key recommendations for improving maintenance effectiveness. The findings in this study are expected to provide theoretical and practical contributions for sports facility managers, especially tennis courts, in designing more efficient, safe and sustainable management strategies.